1939 Ferriday archtop: A dream guitar. (8th April 2016) - Johanis, Paul
Abstract : In 2015, the Canadian author is gifted a mystery guitar made in London, August 1939. The article tracks down its origin and story, which is interwoven with the development of the early jazz scene in England.